Interactions of polydispersed single-walled carbon nanotubes with T cells resulting in downregulation of allogeneic CTL responses in vitro and in vivo. Issue 8 (December 2012) - Alam, Anwar; Sachar, Sumedha; Puri, Niti; Saxena, Rajiv K.
Abstract Addition of polydispersed acid functionalised single-walled carbon nanotubes (AF-SWCNTs) significantly suppressed alloimmune cytotoxic T cell (CTL) response generated in a mixed lymphocyte reaction (MLR) between spleen cells from C57BL/6 (H-2b) and BALB/c (H-2d) mice. AF-SWCNTs treatment also decreased CD69 expression, enhanced apoptotic response in T cells and reduced significantly the recovery of live CD4+ and CD8+ T cells from MLR cultures. A two to threefold increase was noticed in the binding/uptake of AF-SWCNTs by T cells in MLR cultures as compared with control cultured T cells. Confocal microscopy confirmed the internalization of AF-SWCNTs by live CD8+ T cells in MLR cultures. Administration of AF-SWCNTs suppressed the generation of anti-P815 CTL response in C57BL/6 mice and the recovery of T-cell populations from the spleens. The results demonstrate a suppressive effect of AF-SWCNTs on CTL response and provide an insight into the mechanism of this suppression.